DETERMINATION OF CRITICAL COMPONENTS FOR NAVIGATION RADAR USING FUZZY FMEA AND TOPSIS - Okol S Suharyo; Avando Bastari; Abdul Rahman (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
In determining the critical components and repair priorities, traditional FMEA still have weaknesses, which puts the traditional FMEA factor severity, occurance and detection at the same level of importance, despite the fact that have different levels of interest and importance weight FMEA assessment teams are ignored. In this study integrated fuzzy method in which the FMEA factor severity, occurance and detection assessed in the form of linguistics. At this fuzzy method, the weight of the assessment team FMEA interests are taken into account. To do perangkingan and priority repair used method Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) based on criteria such as level of risk, economic costs, availability of spare parts, maintenance of economic safety and personal abilities. Application of Fuzzy and TOPSIS method in the FMEA to determine the critical components and priorities of the various alternative repair elected to damage components applied to Sperry Marine Navigation Radar system, which is expected by the application of this method can improve operational performance KRI to keep the areas of national jurisdiction